2018
DOI: 10.3747/pdi.2017.00271
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenia and Frailty in PD: Impact on Mortality, Malnutrition, and Inflammation

Abstract: The presence of sarcopenia or frailty was associated with a worse prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
77
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(85 citation statements)
references
References 27 publications
4
77
0
4
Order By: Relevance
“…In that regard, sarcopenic subjects identified using the EWGSOP criteria were associated with a reduction in BMI. The fact that BMI was lower in patients with low ASMI was recently confirmed by Fonseca et al [ 28 ], who evaluated 168 male subjects characterized by different weights and heights, in addition to observations reported in the literature [ 29 , 30 ]. In our study, patients with low ASMI, according to the Tengvall criteria, were associated with a larger number of risk factors.…”
Section: Discussionmentioning
confidence: 60%
“…In that regard, sarcopenic subjects identified using the EWGSOP criteria were associated with a reduction in BMI. The fact that BMI was lower in patients with low ASMI was recently confirmed by Fonseca et al [ 28 ], who evaluated 168 male subjects characterized by different weights and heights, in addition to observations reported in the literature [ 29 , 30 ]. In our study, patients with low ASMI, according to the Tengvall criteria, were associated with a larger number of risk factors.…”
Section: Discussionmentioning
confidence: 60%
“…Malnutrition often occurs in severe acute stroke patients who are unable to take foods orally due to dysphagia or disturbed level of consciousness and who must receive enteral tube feeding (ETF) [ 1 – 3 ]. Malnutrition leads to the severity of the general condition and subsequently extended stay in hospital or in-hospital mortality [ 4 7 ]. Malnutrition may contribute to a weakened immune system and causes infection to occur [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, several parameters associated with RRF including serum albumin, CRP, HDL cholesterol, and HOMA‐IR were significantly altered in the exercise group compared with the findings in the usual care group. A previous observational study reported that MIA syndrome was related to sarcopenia, which predicted a high risk for mortality in patients undergoing PD 34 . Additionally, MIA syndrome in patients receiving PD might be associated with the development of uremic encephalopathy 35 .…”
Section: Discussionmentioning
confidence: 98%